Textile surface design: a study of the geometrical knowledge in African American Freedom Quilts (ModaPalavra e-periódico, 2016)
This paper discusses the presence of materials, technical and technological knowledge originating in the African culture in surface and textile construction work through the analysis of geometric patterns and their compositions derived, present in work with the quilt technique. This relationship is discussed from the perspective of geometry and the textile surface design showing how reflection on the ethnic and cultural diversity can contribute to the affirmation and appreciation of certain crops and theirknowledge that, in many instances, are rootless and wrongly attributed the European and euro descendants cultures. This paper seeks to highlight the African origin of some geometric patterns lavishly designed in textile surfaces, often played, taught and disseminated without their proper provenances are granted. This reflection will demonstrate the contributions of African culture and African descent in the textile surface design, legitimizing the systematization of knowledge and African knowledge that canbe understood through the study of its artifacts.
Keywords: surface textile design; knowledge; African and Afro-descendant culture